Penggunaan Media Pembelajaran Audio Visual dalam Mata Pelajaran PKn - Faizah Faizah (Universitas Negeri Medan, 2017)
To improve student learning outcomes on Civics subjects about the consequences of not maintaining the environment, the researchers used Audio Visual learning media. This research uses classroom action research method with two cycles. Each cycle consists of planning, action, observation, and reflection. Data collection is done by test. The data collection tools used are questionnaires, observation, and documentation. Data analysis techniques used are quantitative and qualitative techniques. The results showed that, learning result data obtained by learners in cycle I mean 83 (good) and experience increase in cycle II average 92,23 (very good). And for student motivation on audio visual learning media in cycle I is 80% (good) while in cycle II equal to 90,6% (good). Overall the value obtained for each aspect of the statement in the questionnaire has increased. Based on the results of these studies, it is evident that the application of the use of audio visual learning media on learning Civics can improve student learning outcomes. Therefore, the researcher recommends that classroom teachers use audio-visual learning media in classroom teaching.